Production improvement through work study techniques / Zainoor Hailmee Solihin and Mohd Fadzrul Ahmad - Solihin, Zainoor Hailmee; Ahmad, Mohd Fadzrul (2004)
This final project entitles 'Production Improvement Through Work Study Techniques' is being made in T&K Autopart Sdn Bhd in Subang High Tech, Shah Alam. T&K Autopart is producing steering for Toyota Camry, Toyota Unser and many more. Our project will be based upon the assembly of End Tie Rod which is one of the components in the power and manual steering. As customer demand increase from 2000 pieces per day to 3000 pieces per day, the assembly of End Tie Rod will be improved from 24 second to 18 second. We also try to identify the inefficiency in the production, so that customer requirement can be met. As improvement is the objective, here we use work study techniques as a tool for production improvement. The first term used is to select and record the process of assembly End Tie Rod. After the selecting and recording process is done, we will proceed to do time measurement which is to find the standard rating for cycle time. This method will be explained detailed in chapter 3. In chapter 4, the process of examine will be done where we will locate the inefficiency occur in the production line and try to solve the problem. This requires brainstorming process. Chapter 5 will deal with Develop which is to develop a new method for improvement. As in Chapter 4 we have defined the problem that occurs and action taken, here in Chapter 5 we develop the improvement. Lastly in Chapter 6 is Install and Maintain which is to check whether our improvement is has real benefits and attaining high efficiency to the production. In the result section, we will show the increasing in the production output from regular 24 second compare to 18 second. Here we will show the increasing in profit that we can gain from the improvement carried out. Further to this, the increased in productivity and efficiency after the improvement will be shown with discussion and concluding remark.